Battlestar Galactica. Season 4.5 [videorecording (DVD)] - Olmos, Edward James; McDonnell, Mary; Sackhoff, Katee; Bamber, Jamie, 1973-; Callis, James; Helfer, Tricia; Olmos, Bodie, 1975-; Stockwell, Dean, 1938-; Bennett, Matthew, 1954- (Universal Studios Home Entertainment, 2009)
From their initial action-packed battles against the Cylons to their desperate attempts to find the fabled 13th colony, Earth, the determined band of human survivors continue to fight for their lives and their hopes. Join them now as the fleet journeys into the furthest reaches of unexplored space.